2015
DOI: 10.5465/amj.2011.0829
|View full text |Cite
|
Sign up to set email alerts
|

Cracking but not Breaking: Joint Effects of Faultline Strength and Diversity Climate on Loyal Behavior

Abstract: This study examines the joint effects of diversity composition (as manifested in faultline strength) and diversity management (as manifested in diversity climate) on loyal behavior. Using data gathered from a sample of 1,652 managerial employees in 76 work units, we assessed the crosslevel effects of unit-level relationship-and task-related faultline strength and diversity climate on individual-level loyal behavior of managerial employees. We found a negative relationship between gender faultline strength and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
116
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 112 publications
(122 citation statements)
references
References 103 publications
4
116
0
2
Order By: Relevance
“…As hypothesized, we observe negative effects for gender (albeit modest) and educational‐level faultline strength and positive effects for functional‐background and tenure faultline strength in the TMT contexts. Accordingly, we join a recent body of research suggesting that attention should be given to different faultline types (Bezrukova et al, ) and to apply such assumptions in studying TMTs (Hutzschenreuter & Horstkotte, ), albeit in a fine‐grained way (Chung et al, ).…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…As hypothesized, we observe negative effects for gender (albeit modest) and educational‐level faultline strength and positive effects for functional‐background and tenure faultline strength in the TMT contexts. Accordingly, we join a recent body of research suggesting that attention should be given to different faultline types (Bezrukova et al, ) and to apply such assumptions in studying TMTs (Hutzschenreuter & Horstkotte, ), albeit in a fine‐grained way (Chung et al, ).…”
Section: Discussionmentioning
confidence: 75%
“…Drawing on Shaw (), we first created categorical indicators of attributes when calculating faultline strength. The categorical indicators of gender, educational level, functional background, and tenure are classified as follows: gender (male or female); educational level ((a) high school or below, (b) college, (c) university, (d) master's degree, and (e) Ph.D. see Zhu, ); functional background (service roles [sales, marketing, and customer service jobs]; production roles [manufacturing, supply chain, and production jobs], and support roles [human resources, finance, and law]); and TMT tenure ((a) less than 3 years; (b) 3 years but less than 6 years; and (c) more than 6 years; see Chung et al, ). Following Erickson (), we classified age into four groups: (a) individuals born from 1928 to 1945 (Traditionalists); (b) individuals born from 1946 to 1960 (Boomers), (c) Generation X—individuals born from 1961 to 1979; and (d) Generation Y—individuals born from 1980 to 1995.…”
Section: Methodsmentioning
confidence: 99%
“…However, as yet no research has been conducted into faultline activation processes in the context of religious identity at work. We note, however, that with respect to other faultlines, a supportive diversity climate has been found to mitigate their negative consequences and generate loyalty to the larger organization (Chung et al, ), just as team identification has been found to mitigate the effects of faultline activation and enhance team member satisfaction (Jehn & Bezrukova, ). Such findings are promising for insight into the interpersonal dynamics of religious identity at work and for promoting effective diversity management.…”
Section: Discussionmentioning
confidence: 82%
“…Diversity climate refers to the perception employees have of their organization's commitment to recruiting and celebrating people with different backgrounds Chung and Jackson (2015) Academy of Management Journal Shared perceptions among employees in a unit that people are treated fairly and are integrated into work environment regardless of background Buttner and Lowe (2015) Journal of Business Ethics Employee behaviors and attitudes that are grounded in perceptions of the organizational context related to women and minorities Jansen et al (2016) Group Processes and Intergroup Relations…”
Section: Referencementioning
confidence: 99%